Direct observation of light focusing by single photoreceptor cell nuclei - Blaszczak, Zuzanna; Kreysing, Moritz; Guck, Jochen (Optics Express, 2014)
The vertebrate retina is inverted with respect to its optical function, which requires light to pass through the entire tissue prior to detection. The last significant barrier for photons to overcome is the outer nuclear layer formed by photoreceptor cell (PRC) nuclei. Here we experimentally characterise the optical properties of PRC nuclei using bright-field defocusing microscopy to capture near-field intensity distributions behind individual nuclei. We find that some nuclei efficiently focus incident light confirming earlier predictions based on comparative studies of chromatin organisation in nocturnal and diurnal mammals. The emergence of light focusing during the development of mouse nuclei highlights the acquired nature of the observed lens-like behaviour. Optical characterisation of these nuclei is an important first step towards an improved understanding of how light transmission through the retina is influenced by its constituents. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-08-05